Testing f(R)-Theories by Binary Pulsars - Mariafelicia De Laurentis; Ivan De Martino (Acta Polytechnica CTU Proceedings)
Using the Post-Keplerian parameters to obtain, in the Minkowskian limit we obtain constraints on f(R)-theories of gravity from the first time derivative of the orbital period of a sample of binary stars. In the approximation in which the theory is Taylor expandable, we can estimate the parameters of an an analytic f(R)-theory, and fullling the gap between the General Relativity prediction and the one cames from observation, we show that the theory is not ruled out.